Gestational diabetes screening refusal in pregnant women: a cross-sectional survey study - BEKİROĞLU, GÜLNAZ NURAL (My University, 2022)
Objective: Recently, some pregnant women in Türkiye are hesitant to undergo gestational diabetes mellitus (GDM) screening tests and this trend is more common. The objective of the study is to assess the pregnant women’s knowledges, decisions, reasons for hesitations about having the GDM screening tests and test rejection rates. Material and Methods: This cross-sectional study included 647 pregnant women who applied for an antenatal outpatient clinic and who had not yet been diagnosed with GDM and a survey was conducted using questionnaire designed by the authors. Results: At the beginning, 287 (44.4%) of the participants declared that they would have glucose challenge test, 169 (26.1%) would not and 191 (29.5%) were undecided. The rejection rate was lower in those who had knowledge about the screening tests. After a short information about the content of tests, 30% of the women who decided not to have the test and 78.3% of those who were undecided at the beginning, decided to have the test (p=0.001). Conclusion: The knowledge level of pregnant women about diabetes screening and diagnosis influences their decision-making. Organizing well-planned trainings for patients and healthcare professionals using public institutions and media may be effective in reducing the burden of diabetes on social health and the economic indicators.
Keywords: Tıp; Cerrahi Tıp Bilimleri; Kadın Hastalıkları ve Doğum; Sağlık Bilimleri; Temel Tıp Bilimleri; Biyoistatistik ve Tıp Bilişimi; Medicine; Surgery Medicine Sciences; Obstetrics and Gynecology; Health Sciences; Fundamental Medical Sciences; Biostatistics and Medical Informatics; Klinik Tıp (MED); Klinik Tıp; CERRAHİ; TIBBİ BİLİŞİM; KADIN HASTALIKLARI & DOĞUM; TIP, GENEL & DAHİLİ; Clinical Medicine (MED); CLINICAL MEDICINE; SURGERY; MEDICAL INFORMATICS; OBSTETRICS & GYNECOLOGY; MEDICINE, GENERAL & INTERNAL; Genel Sağlık Meslekleri; Patofizyoloji; Temel Bilgi ve Beceriler; Değerlendirme ve Teşhis; Cerrahi; Doğum ve Jinekoloji; Dahiliye; Tıbbi Bilişim; Aile Sağlığı; Tıp (çeşitli); Genel Tıp; General Health Professions; Pathophysiology; Fundamentals and Skills; Assessment and Diagnosis; Surgery; Internal Medicine; Health Informatics; Family Practice; Medicine (miscellaneous); General Medicine; Decision making; diabetes; gestational; diagnostic screening programs; patient education as topic; refusal to participate